Online Interactive Biology Learning System (OIBLS) / Thanendran Vignaswaran - Thanendran, Vignaswaran (2003)
Online Interactive Biology Learning System (OIBLS) is a Web-based Learning-teaching system for upper secondary' school level specifically to students who are taking the Sijil Tinggi Pelajaran Malaysia (STPM). Upper secondary school students and teachers are the target of this system. It can be a teaching tool or as a self-learning program. The strength if OIBLS is that it provides lessons to educate users on the meaning of Biology specifying on the topics namely Life Processes, Green Plants, Humans as Organism, Variation, Inheritance and Evolution. There are tutorials that test the student's and worksheets that can be downloaded for further practice. Games based on the topics will be created for students to increase the interest of learning Biology and to test their skills. This project aims to create an effective and interesting learning tool to enable students learn and enjoy Biology at the same time. OIBLS, is a web-based application could increase the number of computer literate students through an interactive and interesting way oflearning Biology. The waterfall model with prototyping will be development model used to develop OIBLS. The main advantage of this system is that the process can be tailored to meet the specific requirements yet possibly changing needs of any application. As OIBLS is an interactive multimedia web-based system, tools that will be used for the development comprises of Macromedia Flash 5, Macromedia Dreamweaver 4, and Adobe Photoshop, ASP, HTML and Java Script are the programming languages that will be used and Microsoft Access 2000 serves as the database to store information of the system.